2022
DOI: 10.3390/life12111695
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Probiotic Enterococcus faecium on Muscle Characteristics of Chickens

Abstract: The use of antibiotics in farm animals is one of the main reasons for the development of resistant bacterial strains (e.g., zoonotic pathogens). Therefore, save alternatives are needed. Here, we examined how post-hatch application (day one to seven of life) of the probiotic Enterococcus faecium AL41 (EF) affects the development and tissue properties of the broiler pectoralis major muscle (PM). Expression of regulators, namely IGF-1, PAX7, and MYF5, was also investigated. At day 1 (n = 6), and days 5, 8, and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
1
3
0
Order By: Relevance
“…Past research has lauded E. hirae for its potential probiotic properties and diverse antimicrobial activities [55,56]. Likewise, the probiotic capabilities of E. faecium have been thoroughly documented, from its bacteriocin production to its positive effects on epithelial integrity [57,58]. The collective findings from these highlighted studies affirm the alignment of our research with substantial potential for the identified LAB strains from the goat intestine.…”
Section: Discussionsupporting
confidence: 71%
“…Past research has lauded E. hirae for its potential probiotic properties and diverse antimicrobial activities [55,56]. Likewise, the probiotic capabilities of E. faecium have been thoroughly documented, from its bacteriocin production to its positive effects on epithelial integrity [57,58]. The collective findings from these highlighted studies affirm the alignment of our research with substantial potential for the identified LAB strains from the goat intestine.…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, even the administration of L. fermentum 2i3 alone did not have a sufficiently stimulating effect on the gene expression of these factors. Notably, in our recent study by Albrecht et al 2022 , we found that another probiotic strain, Enterococcus faecium AL41, had only a temporary stimulatory effect on IGF-1 gene expression, which declined as the chickens aged, and in contrast, had a strong effect on PAX-7 expression. These results may indicate different effects of individual probiotic strains at the molecular level of the growth factors in the pectoral muscle.…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have also shown that probiotics exert beneficial effects on the muscle growth of broiler chickens ( Shah et al , 2019 ; Stasiak et al , 2021 ). Dietary supplementation with Enterococcus faecium AL41 increased the number of myonuclei per fiber, improved capillarization, and further improved body weight owing to the high intramuscular expression of IGF-1 and lowered MYF5 expression in broilers ( Albrecht et al , 2022 ). In addition, microbiota dysbiosis may induce neuroinflammation via the microbiota–gut–brain axis, which causes injurious behaviors in chickens ( Jiang et al , 2022 ; Shamshirgaran et al , 2022 ).…”
Section: Beneficial Properties and Applications Of Probiotics In Chic...mentioning
confidence: 99%